An examination of the mediating role of maladaptive emotion regulation strategies in the complex relationship between interpersonal needs and suicidal behavior - Abdollahpour Ranjbar, Hamed; Bakhshesh-Boroujeni, Michael; Farajpour-Niri, Sepideh; Hekmati, Issa; Habibi Asgarabad, Mojtaba; Eskin, Mehmet (Frontiers in Psychiatry, 2024)
Background Studies have shown that psychological factors, notably interpersonal needs and emotion regulation, play a significant role in suicidal behavior. Interpersonal needs are significant contextual components that affect emotion regulation and contribute to a wide range of dysfunctional behaviors, such as suicidal behavior. It has been postulated that emotion regulation mediates the associations between proximal and distal risk factors of suicidal behavior. Method The sample consisted of 340 community-dwelling individuals (62.5% women; SD = 0.48) with an age range of 18 through 55 (M = 30.23; SD = 8.54) who completed the interpersonal needs questionnaire, the suicide behaviors questionnaire-revised, and the cognitive emotion regulation questionnaire. The Structural Equation Modeling (SEM) approach was utilized to evaluate a mediation model. Results The findings indicate that interpersonal needs (i.e., perceived burdensomeness r = .55, p <.01 and thwarted belongingness r = .25, p <.01) and putatively maladaptive cognitive emotion regulation strategies (i.e., self-blame; r = .38, p <.01, catastrophizing; r = .55, p <.01, rumination; r = .40, p <.01, and other blame; r = .44, p <.01) have strong associations with suicidal behavior, and these strategies have a mediating effect on the association between interpersonal needs and suicidal behavior. Conclusions Our findings show that contextual-interpersonal needs, which underpin suicidal behavior, are significantly influenced by maladaptive emotional processes. Thus, therapeutic outcomes might be enhanced by focusing on the content of the associated cognitions and trying to reduce maladaptive regulatory processes like rumination and catastrophization.